Demandas física e fisiológica em diferentes pequenos jogos de basquetebol - Sarah da Gloria Teles Bredt (2017)
The objectives of this study were 1) to compare the physical (accelerations) and physiological (heart rate) demands of three different 3vs.3 basketball small-sided games (SSG) performed in half court: 3vs.3 with man-to-man defense in half playing area (3vs.3HALF), 3vs.3 with man-to-man defense in full playing area (3vs.3FULL), and 3vs.3 with reduced time to make the shot (3vs.3RT); and 2) to measure reliability of variables related to physical and physiological demands in the 3vs.3HALF. Twelve male U17 athletes of a sports club were divided into four teams of three players, which randomly played all SSG (two bouts of five minutes) against each other during six sessions. All 3vs.3HALF SSG were peformed twice in order to calculate test-retest reliability. For measuring physical demand, athletes wore a elastic belt with a pocket containing a wireless triaxial accelerometer, which recorded all accelerations performed by athletes during the SSG. Variables related to physiological demand were calculated based on heart rate (HR) data recorded by heart rate monitors used by athletes during SSG. The 3vs.3FULL and 3vs.3RT SSG presented higher physical demand relative to resultant acceleration. Analysis of accelerations in the three movement axes also showed that both 3vs.3FULL and 3vs.3RT SSG presented significantly higher intensity of accelerations performed in vertical axis, possibly due to the increased number of shots peformed in the 3vs.3RT and increased number of fakes in the 3vs.3FULL. However, 3vs.3RT presented significantly lower intensity of accelerations in the anteroposterior axis, which might be related to the increase in the number of individual tactical actions performed by players in this SSG. Variables related to physiological demand did not present differences among SSG. The 3vs.3HALF SSG presented good relative and absolute reliability for several variables related to physical and physiological demands, which suggest that coaches and physical trainers can expect good reproducibility of athletes scores (standard error of measurement) and also that there is a great variability between athletes scores and that the ranking of these scores is consistent among repeated trials of the 3vs.3HALF SSG.